Auditory, visual and proprioceptive integration as a substrate of language development (2018)
Introduction: Language development is a complex process that may be considered as an evolutionay trait in human beings; it is possible to undetstand said process by evaluating the contribution of sensory systems and the events that frame critical periods of development. Objective: To conduct a literature on how auditory, visual and proprioceptive information integration occurs in language development, as well as the role of social interaction in this process. Materals and methods: The MeSH terms “Language Development”; “Visual Perception”; “Hearing”; and “Proprioception” were used, limiting the main search to articles written in English, Spanish and Portuguese. The databases consulted were Medline and EMBASE. Results: Auditory information is the first sensory stimulus to consider because, during the first year of life, the infant recognizes and discriminates environmental signals that correspond to language, followed by a peak in its acquisition and, subsequently, by a stage of maximum linguistic discrimination. Visual information allows correlating language with images since it acts as the substrate for the designation and understanding of words, as well as for interpretation and imitation of the emotional component in gesticulation. Proprioceptive information provides feedback on motor performance patterns used in language production. Conclusion: This perspective offers new points of view for treating and managing deviations in language development. © 2018, Universidad Nacional de Colombia. All rights reserved.